SOCIAL AND ECONOMIC SITUATION OF THE NORTHEAST CAUCASUS IN THE FIRST HALF OF THE NINETEENTH CENTURY - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the socioeconomic development of the peoples of the Northeast Caucasus during the first half of the nineteenth century. Employing a comparative historical method, the study highlights both commonalities and regional specificities in economic organization and social stratification. The analysis demonstrates that while the regional economy was fundamentally agrarian, distinct zonal specializations emerged: livestock farming dominated the mountainous regions, whereas arable agriculture prevailed in the plains. Artisanal production reached varying degrees of sophistication, particularly in wool processing—yielding cloth, carpets, rugs, felt, and saddlebags—and metallurgy, with highlanders renowned for manufacturing bladed weapons and firearms. Commercial activity evolved primarily through barter, characterized by the exchange of agricultural surplus for handcrafted goods. Key trading centers included Terek for Dagestani populations and Vladikavkaz for the Ingush. In Dagestan, commercial expansion was further supported by road construction and the establishment of exchange houses, with Derbent playing a pivotal role as a maritime trade link to Astrakhan. The analysis further delineates the heterogeneous social structures of the region. In Dagestan, established feudal relations created a hierarchy comprising rulers (shamkhals, khans), free uzdens, dependent peasantry, and slaves. In contrast, Chechen and Ingush societies were characterized by the disintegration of traditional clan systems, consisting primarily of free community members with a limited slave population. The study also addresses the consequences of Tsarist military expansion, which subjected the local population to intensified oppression through land confiscation, the destruction of settlements and agriculture, and economic blockades. These punitive measures severely disrupted regional economic development and precipitated armed resistance. The article concludes that while the peoples of the Northeast Caucasus shared a common economic foundation in agriculture and handicrafts, their social trajectories diverged significantly, ranging from the feudal stratification of Dagestan to the transforming tribal structures of the Chechens and Ingush.
Keywords: economy; social stratification; feudal oppression; arrival of tsarist troops; punitive expeditions